Swift and certain probation: Assessing fidelity to the HOPE model1. (December 2020) - Frailing, Kelly; Kennedy, Jahdai; Taylor, Rae; Rapp, Victoria
While outcomes for HOPE and HOPE-like probation programs have received a good deal of attention in the literature, there is arguably less focus on implementation of those programs with fidelity to the HOPE model. This study describes one such program, the Swift and Certain Probation program in Jefferson Parish, Louisiana, and the degree to which it was implemented with fidelity using the list of elements laid out in the Demonstration Field Experiment (DFE) Final Report. We observed the Swift and Certain Probation program for two years and found that it is implemented with fidelity across many, but not all, of the elements of HOPE. We conclude with lingering issues for both the implementation and evaluation of HOPE and, especially, HOPE-like programs.